Impulsive buying behavior of millennial TikTok users in the view of Al-Ghazali's maqasid syariah: A study of millennials in West Kalimantan - Holil, Muhammad; Yandi, Pitri (Asy-Syari’ah : Jurnal Hukum Islam, 2026)
The phenomenon of impulse buying on TikTok's Live Shopping feature is increasing among millennials, including in West Kalimantan, in line with the rise of visual-based marketing, flash sales, and real-time interactions. This behavior has the potential to lead to irrational purchasing decisions, so it needs to be studied from the perspective of Al-Ghazali's Maqasid Syariah, particularly in relation to the preservation of wealth (hifz al-mal) and self-control. This study aims to analyze the psychological influence of consumers, social media in purchasing, as well as financial planning and self-control on impulse buying among TikTok Live Shopping users, while assessing its suitability with the principles of Maqasid Syariah. The study uses a mixed method with a quantitative approach through SEM-PLS (SmartPLS 4) and a qualitative approach through in-depth interviews. The sample consisted of 140 millennial respondents in West Kalimantan who actively use TikTok. The outer model evaluation showed that all indicators were valid with a loading factor value ≥ 0.70. The inner model results showed that consumer psychology had a significant effect on impulse buying (β = 0.288; p = 0.001), social media significantly influences purchasing (β = 0.301; p = 0.000), and financial planning and self-control are the most dominant factors (β = 0.386; p = 0.000). Qualitative findings reinforce the statistical results, in which informants admitted to being driven to buy due to visual stimuli, social pressure from comments and shopping notifications, and weak self-control while watching live streams. The results of this study show that impulse buying behavior on TikTok tends to be inconsistent with Al-Ghazali's Maqasid Syariah, especially in terms of protecting property and controlling desires. The novelty of this research lies in the integration of digital consumer behavior analysis through SEM-PLS with a normative evaluation of Maqasid Syariah in the context of TikTok Live Shopping. This research is expected to contribute to the literature on digital Islamic economics and serve as a basis for financial literacy and Islamic consumption education for the millennial generation.